SISTEM PENGHANGAT DAN PENDINGIN PADA PETERNAKAN AYAM - Sahrial; Yuliardi Kurniawan; Aan Febriansyah; Yudhi Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The Heating and Cooling System is a Temperature Controller in the brooding system ofchicken farms. Temperature determines the success of broiler breeders, especially in thebrooding period. If the heating and cooling system is not met, then the performance of thechickens can be problematic and can even cause high mortality. Thus, a heating and coolingcontrol device is urgently needed, with the problem of how to plan, implement and test theresults of temperature control in broiler chicken coops for brooding period automaticallybased on Arduino-Uno whether it is in accordance with the setpoint. The purpose of thisresearch is to be able to plan, implement and obtain test results in accordance with theplanning of this heating and cooling system. The method used isexperimental researchmethods,including1)systemconceptdevelopment,2)systemplanning,3)heatingandcooling system implementationand 4) heatingand cooling temperature testing. Analysis ofthe results is carried out by checking the heating and cooling temperatures planned with thevalue of the test results of the tool. The results show that they are able to plan the requiredtemperaturebased onArduinoinabroilerchickencoop duringthe brooding periode